Strategi pencegahan obesitas pada anak SDN 02 wilayah puskesmas rambah Kabupaten Rokan Hulu - Junita, Elvira (Jurnal Martenity and Neonatal, 2016)
The incidence of obesity in children is increasing. If it does not do the prevention and treatment of early age, children with overweight or obese will grow into adults who are obese. The condition puts them at high risk to health (Diana, 2012). If both parents are obese, about 80% of their children will be obese and if both parents areÂ obese, the prevalence of obesity will drop to 14%. Data from the World Health Organization (WHO) showed that in 2010, approximately 43 million children under five are overweight. Nearly 35 million children are overweight live in developing countries. The remaining 8 million, is in the developed countries (Diana, 2012). Data school-age children who are obese gained from networking to schools in PuskesmasRokanHulu. There are 33 government-owned primary school and three elementary schools Private Owned in PuskesmasRambah. Of the netting was found that many children who are obese. Especially in elementary school.SD N 02 Rambah there are students from Grades 4, 5 and 6 have as many as 215 students, and 31 children with obersitas. This type of research is a quantitative research study to design analytic cross-sectional study. For this study the overall population sampled (total sampling) is 215. Analysis of data using analysis univariat, bivariat with a statistical test of chi-square p <0.05 and multivariate linear regression Ganda. Multivariate analysis showed there was a significant relationship between physical activity / exercise value OR of 5.8 (95% CI 2.20 to 15.30), activity watch TV / games value OR of 6.5 (95% CI 2.4, -17, 78), consumption fastfoods / junkfoods value OR 5.8 (95% CI 2.25 to 15.36), the value of energy intake OR 8.9 (95% CI 2.8 to 28.3). It is suggested that the child should be limited in time ren when at home watching / playing of games. where school age children recommended total television time is not more than 2 hours a day.